2017
DOI: 10.1016/j.joen.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative Endodontic Therapy in the Management of Nonvital Immature Permanent Teeth: A Systematic Review—Outcome Evaluation and Meta-analysis

Abstract: Many knowledge gaps still exist within the studies published. Current published evidence is unable to provide definitive conclusions on the predictability of RET outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 22 publications
1
77
0
2
Order By: Relevance
“…, Tong et al . ). It was believed that RET was capable of regenerating the pulp–dentine complex to restore the vitality of tissue damaged in the canal space and increase thickness of the canal walls to strengthen the fragile immature permanent teeth (Iwaya et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…, Tong et al . ). It was believed that RET was capable of regenerating the pulp–dentine complex to restore the vitality of tissue damaged in the canal space and increase thickness of the canal walls to strengthen the fragile immature permanent teeth (Iwaya et al .…”
Section: Discussionmentioning
confidence: 97%
“…Two recent systematic reviews (Tong et al . , Torabinejad et al . ) demonstrated that the primary goal of RET could be reliably achieved with high probabilities (91–94% of periapical healing).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently published systematic review and meta‐analysis have shown that current published evidence is unable to provide definitive conclusions on the predictability of this technique (Tong et al . ). Indeed prospective studies have failed to predictably demonstrate any significant hard tissue gain in the root canal system (Nazzal et al .…”
Section: Discussionmentioning
confidence: 97%